استطلاع آراء الشباب السعودي حول البرنامج الإرشادي قبل الزواج - بن عسكر, د. منصور بن عبد الرحمن; بن عسكر, د. منصور بن عبد الرحمن; السبيله, أ. مشاري بن عبد الهادي (دفـاتر المـــــــــــخبـر, 2018)
يعد الزواج أحد الحالات التي تتطلب دورا جديدا يسمح بالمشاركة في اتخاذ القرارات وحل المشكلات وهذا يتطلب بعض التغيير في سلوك الفرد وعاداته. حيث يعتمد أداء الدور على مستوى الاستعداد لدى الشاب المقبل على الزواج ومدى تفهم الشريك له والتوقعات حول ذلك الدور. ومن هنا تأتي أهمية البرنامج الإرشادي لدى مشروع ابن باز الخيري ليكون ملبياً للشباب المقبل على الزواج من حيث حاجاته ومطالبه وتساؤلاته حول كيفية اختيار شريك الحياة، وطبيعة العلاقة الزواجية، والتغيرات النفسية والجسمية التي تحدث للزوجين، والقواعد الشرعية التي تنظم علاقة الزوجين، ومسالة القوامة والإنفاق، والدور المنوط بكلا الزوجين لاستقامة الحياة الأسرية، وحدود العلاقة مع الأهل، وأسلوب الإنفاق، حيث استهدفت الدراسة التعرف على مدى استفادة الشباب المقبلين على الزواج من البرنامج الإرشادي المقام في مشروع ابن باز الخيري في الرياض. ولتحقيق هذا الهدف تم إعداد استمارة صممت من واقع البرنامج الإرشادي في المشروع، وتم تطبيقها على 77 شاب مقبل على الزواج من الملتحقين في البرنامج باستخدام أسلوب الحصر الشامل، وقد توصلت الدراسة إلى عدد من النتائج والتي من أهمها أن هناك استفادة بدرجة كبيرة من البرنامج في محاوره الخمسة (الشرعية-الاجتماعية-النفسية-الصحية-الاقتصادية-الجنسية)   Abstract Marriage is a situation where a new role is created involving sharing in decision making and problem solving. This role entails a change in the individual’s behaviour and habits. It depends mainly on the young man’s attitude before marriage and how the partner understands that and what expectations are related to that role. Hence comes the importance of the IbnBaz Counselling Program, fulfilling the needs and addressing the main questions of the young people planning to marry, in terms of selecting the partner, the nature of the marriage relationship, the psychological and physical changes involved in marriage, the legislative rules regulating the relationship, leadership and expenditure, the roles expected from each partner, the relationship with parents, and the spending strategies. The study aims at getting feedback of the young people participating in the project. For this purpose, a form was created and distributed among 77 young men participating in the program and planning to get married, using the comprehensive exclusiveness method. The survey showed that there was great benefit for the young people from the program with its six aspects: the legislative, the social, the psychological, the health,the economical, and the sexual. The study has later come up with a few recommendations for some concerned associations in thematter.